Progress in the Development of Anti-tissue Factor Pathway Inhibitors for Haemophilia Management - Mahlangu, Johnny N. (Frontiers in Medicine, 2021)
Abstract The unprecedented progress in addressing unmet needs in haemophilia care to date includes developing several novel therapies that rebalance haemostasis by restoring thrombin generation in patients with haemophilia A or B with and without inhibitors. These novel therapies are FVIII mimetics, antithrombin interference RNA therapy and several monoclonal antibodies directed against the tissue factor pathway inhibitor(anti-TFPI). In this review, we provide an update on the progress made in developing anti-TFPI therapie. Phase 1 data from the three anti-TFPI studies showed acceptable safety profiles, and currently, available phase 2 data are encouraging. While these data support these molecules' further development progression, there is uncertainty on several aspects of their evolution. Two of the three anti-TFPIs have shown drug-related thrombosis, with one study consequently terminated. None of the thrombotic events is predictable with current monitoring tools, and none correlate with known coagulation parameters. All three anti-TFPIs undergo target mediated drug disposition, which impacts the formulation of dosing regimen fo these therapies. They would require more frequent than some of the extended half-life clotting factor products and antithrombin RNAi therapy. There is no assay to measure the TFPI as the physiological levels are very low, which makes monitoring the impact of the anti-TFPI a challenge. The anti-TFPIs have several advantages, including their bioavailability when administered subcutaneously, their stable pharmacokinetics and their ability to prevent bleeds in haemophilia A or B patients with and without inhibitors. Whether these advantages can be realized will depend on the outcome of the currently ongoing studies.